Pollutant emissions from modern incinerators. (1st January 2002) - Lima, Rui; Bachmann, Robert T.
Emissions of dioxins are mainly from incinerators, domestic and industrial coal combustion, and traffic. However, the major public concern and research effort are associated with the emissions of organic micropollutants from waste incinerators. This paper gives a brief overview of the more recent research and development for the removal of dioxins and heavy metals from flue-gas streams. Special attention is devoted to the origin and control of emissions from incinerators. It appears that flue-gas cleaning systems in modern incinerators are very reliable in removing almost all polluting emissions from flue-gas streams. However, the fly ash residues generated pose a significant disposal problem, as they are enriched with heavy metals and organic micropollutants.